Experimental study on curved finned horizontal cylinders under natural convection - Kim, Donghyuk; Kim, Dong Kwon (Applied Thermal Engineering, 2024)
Radially finned cylinders under natural convection are widely used for reliable cooling of cylindrical electronic products, including LED lightings. These radially finned cylinders need to exhibit high cooling performance regardless of orientation, making the thermal performance when installed horizontally crucial. Consequently, there has been research on horizontal finned cylinders, including studies aimed at enhancing their thermal performance using perforated fins or cross-cut fins. However, systematic research on improving the thermal performance of horizontal finned cylinders under natural convection using curved fins has not been conducted. In this study, a systematic experimental investigation is conducted for the first time on the thermal performance of a curved finned horizontal cylinder under natural convection. Experiments are performed to measure the heat transfer rate from the finned cylinder to the surroundings, varying the cylinder temperature, fin number, and fin height. Based on the experimental results, a correlation for the Nusselt number is proposed, which can predict the convective heat transfer coefficient within a 10% error margin when the Rayleigh number is between 20 and 50000. The accuracy of the correlation proposed in this study is compared with the accuracy of correlations for various types of heat sinks that have been proposed in previous studies. While existing correlations exhibit significant errors and fail to predict the experimental results for curved-finned cylinders accurately, the correlation proposed in this study precisely predicts the experimental data. During this comparison of correlations, various characteristics of natural convection phenomena occurring in curved-finned cylinders are also examined. The proposed correlation is used to investigate the effects of fin height, fin number, and fin thickness on thermal performance. Additionally, using the proposed correlation, the optimal fin number and fin thickness for maximizing thermal performance are identified. Finally, the thermal performance of the curved finned horizontal cylinder is compared with that of a traditional finned horizontal cylinder, demonstrating that the former exhibits a 20% improvement in thermal performance over the latter.
Keywords: Curved plate fin; Curved plates; Fin height; Fin numbers; Fin thickness; Finned cylinder; Horizontal cylinders; Plate fins; Reliable cooling; Thermal Performance; Curved plate fins; Horizontal cylinders; Natural convection